Diagnóstico de la cobertura vegetal del permanente de bosque existente en el sitio Huizho, parroquia Casacay, cantón Pasaje, provincia de El Oro - Álvarez Peñaranda, Carolina Cecibel (Machala : Universidad Técnica de Machala, 2014)
The research work aims to investigate the State of the vegetation cover of the remnant forest located in the sector Huizho, Casacay parish, province of El Oro, given its environmental importance to the Pasaje canton. The methodology applied in the investigation left the application of the scientific method and techniques such as survey and interview. The work contains a diagnosis of the vegetation of the forest remnants, their degree of preservation and conservation. It includes also important conceptualizations in the environmental order related to the hydrographic sub-basin of the river Huizho, the hydrology of the Pasaje canton, the risks and challenges that presents the remnants being part of a protected area. It includes a critical analysis of the problem of research as well as analysis and interpretation of the results of the empirical research culminating in the verification of the hypothesis.
Keywords: DIAGNOSTICO; VEGETAL; BOSQUE; GESTION AMBIENTAL